Enhancing entrepreneurial intention in secondary school - Kakava, Eunah; Eta, Marima; Shepherd, Murebwa (Journal of Sustainable Tourism and Entrepreneurship, 2023)
Purpose: The literature reveals that emerging markets experience high unemployment rates. However, tertiary institutions continue to chant out a large number of graduates, increasing the rate of unemployment. Regardless of the tertiary institutions introducing entrepreneurship education, graduates continue to seek employment instead of creating it. This study analyses the introduction of entrepreneurship education in secondary schools to create entrepreneurship intentions in students. Research Methodology:  The researcher adopted an interpretative paradigm that advocates a qualitative approach. The study face-to-face interviewed 17 head teachers from secondary schools in the Mashonaland West Province.  This study thematically deduces entrepreneurship teaching methods, entrepreneurship content, and entrepreneurship assessment methods as sub-concepts that, if implemented, lead to entrepreneurship intention. Results: The researcher established that entrepreneurship education leads to entrepreneurship intentions if introduced in secondary schools. However, it requires commitment from policy designers and implementers to achieve the intended goals.  This study recommends the adoption of entrepreneurship education based on a funding model supported by stakeholders, including financial institutions and the government. Limitations: The study had a methodological limitation in that the sample size was small (17 head teachers). Contributions: This study contributes to educational policy changes through the introduction of entrepreneurship education and its curriculum. Novelty: This study analyzed the implementation of entrepreneurship education in secondary schools as a vehicle to solve the unemployment challenge.